The Importance of Gold’s Effect on Investment and Predicting the World Gold Price Using the ARIMA and ARIMA-GARCH Model - Bunnag, Tanattrin (Heca Sentra Analitika, 2024)
This paper studies the importance of gold's effect on investment and the fact that gold is often seen as a safe-haven asset during economic uncertainty. When inflation rates rise, investors may turn to gold to preserve their wealth; the government will reserve gold to reduce the exchange rate risk. To provide a comprehensive analysis, the study incorporates forecasting the price of gold using both the Autoregressive Integrated Moving Average (ARIMA) and ARIMA-Generalized Autoregressive Conditional Heteroskedasticity (ARIMA-GARCH) models. The gold price data is daily from 1/01/2021 to 3/01/2024. We perform model comparisons that the ARIMA (2,1,3) and the ARIMA (2,1,3)-GARCH (1,1), which model gives lower mean absolute error (MAE) and root mean squared error (RMSE) values. The results show that the MAE and RMSE predictions of the ARIMA (2,1,3)-GARCH (1,1) model are 80.1371 and 96.8299, better than those of the other model. Therefore, the ARIMA (2,1,3)-GARCH (1,1) model forecast results are better precise. It gives a forecast value for gold prices in the world market at the end of 2024 of 1942.094 USD per troy ounce. Hence, the recommendation for investors and policymakers is that if the price is higher than 1942.094 USD per troy ounce in 2024, investors and policymakers should slow down to buy and wait for it to adjust first, or investors and policymakers with gold should gradually sell to make some profit. Moreover, good portfolio management will reduce the exchange rate risk by including an optimized amount of gold in currency portfolios. However, holding gold is risky; its prices may fluctuate due to factors beyond our control, such as war, uncertainty about world economic growth, and inflation. Therefore, investors and policymakers should consider the abovementioned factors and be careful when hedging in gold.